Aspek Hukum Perlindungan Konsumen Terhadap Air Mineral Merek Arsi di Sibolga - Surbakti, Anton Diary Steward; Natasya, Natasya (LPPM Universitas Ekasakti Padang, 2024)
This research aims to determine the legal aspects of consumer protection for ARSI brand mineral water in Sibolga. The need for clean water is currently increasing while clean water sources are decreasing and for this reason there are AMDK (Bottled Drinking Water) companies that are suitable for consumption by the public. This AMDK company has consumer protection regulated in Law No. 8 of 1999 concerning Consumer Protetion. This research uses normative legal research methods with a statutory approach. The research results concluded that all AMDK companies including ARSI as business actors must fulfil the requirements of applicable laws and regulations as a form of consumer protection.